Geophysical Characterization in the Shallow Water Estuarine Lakes of the Southern Everglades, Florida - Michael Eyob Kiflai; Dean Whitman; René M. Price; Thomas A. Frankovich; Christopher J. Madden (Applied Sciences, 2022)
Anthropogenic activities have greatly modified freshwater flows through Everglades National Park (ENP) such that saltwater has intruded extensively inland from the coastline, causing coastal lakes and their ecosystems to be exposed to varying salinity conditions. The Comprehensive Everglades Restoration Plan (CERP) makes an effort to restore the quantity, quality, timing, and distribution of freshwater flow in ENP with a goal of reducing salinity conditions within the coastal communities and adjacent estuaries. An understanding of the temporal and spatial variations of surface water and shallow groundwater salinity in the coastal lakes of ENP is needed to evaluate restoration efforts. Geophysical surveys were conducted between 2016 to 2019 using electrical resistivity and electromagnetic (EM) methods in the coastal lakes of ENP. A mean local formation factor of 10.7 ± 1.8 was calculated for the region by comparing the lakes’ bottom formation inverted electrical resistivity soundings with coincident pore water resistivity measured in groundwater wells. The conductivity of surface and groundwater increased during the dry season, reflecting decreased precipitation, increased evapotranspiration, and the increasing influence of saline water from Florida Bay. Spatially, salinity in the lakes increased from west to east in the surface water with an opposite trend observed in the shallow groundwater. Along the south to north inland direction, the salinity of both surface water and groundwater decreased. This study demonstrates that floating electrical resistivity and EM methods can characterize the subsurface formation resistivity and describe temporal and spatial patterns of surface and shallow groundwater conductivity.